EDUKASI PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) PADA SISWA SEKOLAH DASAR SDI. FATUFETO 2 KOTA KUPANG - Nggorong, Welmince Paulina (JURNAL MEDIKA USADA, 2025)
Health improvement is one of the national development efforts to achieve awareness, willingness and ability to live healthily for every resident in realizing the highest level of public health. The implementation of health development is directed at increasing awareness, willingness and ability to live healthily for every person to have PHBS in the family, school and community environments. Efforts are needed to educate early childhood to behave in a clean and healthy way, one of which is in the school environment. Clean and Healthy Living Behavior in the school environment is a step to empower students, teachers and the school community so that they can and want to carry out clean and healthy living behaviors in creating healthy schools. The design of this study is descriptive and the number of samples is 50 respondents. The variables in this study are health education for students about healthy and clean living behaviors. Data collection techniques use interview, observation and documentation methods. The results of the study showed that it could increase participants' knowledge and understanding of PHBS where there was an increase in knowledge of 57%. PHBS education activities in schools can be continued in other areas as an effort to foster clean and healthy living behaviors at an early age.